Stability Cogitated Electric Vehicle Charging Infrastructure Planning - Dharmakeerthi, C.H.; Mithulananthan, N. (Department of Electrical Engineering, National Institute of Technology Malang - INDONESIA, 2017)
Electrification of the transportation is taking place at  an  accelerated  rate.  Even  though,  electric  vehicles  (EV) evidently bring numerous environmental and economic benefits, their impact on power systems should not be overlooked. It has been identified that EV load characteristics can significantly affect power system voltage stability and small signal stability. Hence, it is important to consider mitigating of stability impacts right from the  planning  stage  of  bulk  EV  charging  stations.  However, unavailability of suitable stability evaluating indexes that could fit into planning algorithms is a hindrance. This study proposes two computationally  efficient  indexes  to  compare  stability  status  in different  planning  options.  The  developed  indexes  have  been tested, verified and utilized in a multi objective planning algorithm to  identify  a  comprehensive  solution,  which  satisfies  the  grid operator,  EV  customer  and  the  charging  facility  investor optimally.